2019
DOI: 10.1080/1828051x.2019.1585211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean oil supplement to diets of lactating dairy cows, on productive performance, and milk fat acids profile: a meta-analysis

Abstract: The aim of this paper was to investigate the effects of soybean oil, an oilseed rich in the polyunsaturated fatty acid C18:2, on dry matter intake (DMI), milk yield (MY) and milk composition (including fatty acid profile) of dairy cows by using a meta-analysis approach. In the meta-analysis, effect size for all outcomes was reported as standardised means difference with 95% confidence intervals. Q test and I 2 were calculated to detect the heterogeneity, with a metaregression also used to investigate sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
7
14
0
1
Order By: Relevance
“…The negative effect of the dietary inclusion of vegetable oils on cow's milk fat content is well documented in the literature (C. G. S. Ribeiro et al, 2018;Lopes et al, 2019;Mahdavi et al, 2019;Rodrigues et al, 2019). Additionally, the current results corroborate Souza et al (2019) Lopes, F. C. F. et al in the productive performance trial.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The negative effect of the dietary inclusion of vegetable oils on cow's milk fat content is well documented in the literature (C. G. S. Ribeiro et al, 2018;Lopes et al, 2019;Mahdavi et al, 2019;Rodrigues et al, 2019). Additionally, the current results corroborate Souza et al (2019) Lopes, F. C. F. et al in the productive performance trial.…”
Section: Discussionsupporting
confidence: 89%
“…These data corroborate the results of Souza et al (2019) in the productive performance trial. The linear increase in milk protein content (P=0.0242) promoted by SO supports the results from some studies (Rodney, Celi, Scott, Breinhild, & Lean, 2015;Lopes et al, 2019), although the literature commonly indicates that lipid supplementation of diets supplied to cows reduces milk protein content (NRC, 2001;Mahdavi, Mahdavi, Darabighane, Mead, & Lee, 2019). The linear reduction in milk fat content was proportionally higher than the linear increase in milk protein content.…”
Section: Discussionsupporting
confidence: 73%
“…However, the milk protein content was always less than 2.9% (Table 6), which is the minimum value established by Normative Instruction 76. Meta-analysis studies have shown that supplementing the diets of lactating cows with unsaturated FAs (Rabiee et al, 2012;Mahdavi, Mahdavi, Darabighane, Mead, & Lee, 2019) promotes a reduction in milk protein content, likely a result of depressed microbial protein synthesis in the rumen (J. C. Lopes et al, 2017).…”
Section: 48; Tablementioning
confidence: 99%
“…A recent study by Suksombat et al (2016) concluded that supplementation of lactating dairy cows with LO at 2.9% DM in the basal diet (500 g/d) maintaining a 56:44 roughage to concentrate ratio did not alter feed and nutrient intakes. The meta-analysis by Mahdavi et al (2019) showed that DMI was reduced as a result of SO supplementation in the diets of dairy cows. In the present study, buffaloes were fed LO or SO at about 25.6 g/kg of DMI (400 g/ head/d), may not be high enough to reduce DM and nutrient intakes.…”
Section: Dry Matter and Nutrient Intakesmentioning
confidence: 99%
“…Due to the potential health benefits for humans, there is an awareness in augmenting cis-9, trans-11 conjugated linoleic acid (CLA) and polyunsaturated n-3 FA, while decreasing medium-chain FA in the milk of dairy cows through plant oils supplementation (Shingfield et al, 2013;Kairenius et al, 2018;Mahdavi et al, 2019). To our knowledge, the effect of plant oils varying in linoleic or linolenic acid concentrations (soybean oil and linseed oil) on milk composition, milk fatty acids profile, and blood lipid constituents in lactating buffaloes are very limited.…”
Section: Introductionmentioning
confidence: 99%